Heritability estimates for heart and liver visual scores in a male broiler line - Gaya, Leila de Genova; Mourão, Gerson Barreto; Silva, Josineudson Augusto II de Vasconcelos; Rezende, Fernanda Marcondes de; Mattos, Elisângela Chicaroni de; Figueiredo, Luís Gustavo Girardi; Ferraz, José Bento Sterman; Michelan Filho, Tércio; Eler, Joanir Pereira (Brazilian Journal of Veterinary Research and Animal Science, 2006)
The objective of this study was to estimate the heritability coefficients for heart and liver visual scores in a male broiler line. Dataset analysis was realized by restricted maximum likelihood and by R method. Data from 6167 individuals were used. Heart and liver visual scores did not seem to be able to respond to selection, since the heritability estimates obtained by restricted maximum likelihood were 0,05±0,02 for both traits. Possibly due to the low variability of visual scores data, the analyses by R method did not converge.